2012
DOI: 10.3390/molecules171012234
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Synthesis of Modified Pectin Compounds Promoted by Microwave Irradiation

Abstract: Microwave-assisted solvent-free modification of pectin was successfully accomplished, consisting in the esterification of several fatty acids by pectin alcoholic functions. The reaction was performed by simply mixing the reagents with a catalytic amount of the inorganic base (potassium carbonate) and irradiating the obtained mixture with microwaves for a short time (3–6 min). The replacement of the traditional heating with a microwave source allowed the development of a new synthetic protocol which provided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Pectin showed endothermic peaks at 66.5, 244.5, 306.8 and 350.2°C ( Figure 6D ). 54 The DSC curve of guar gum ( Figure 6E ) showed a melting endotherm at 239.5°C which indicates its crystalline nature. 55 Another broad endothermic peak appeared at 80°C corresponding to the hydrophilic groups O-H group.…”
Section: Resultsmentioning
confidence: 95%
“…Pectin showed endothermic peaks at 66.5, 244.5, 306.8 and 350.2°C ( Figure 6D ). 54 The DSC curve of guar gum ( Figure 6E ) showed a melting endotherm at 239.5°C which indicates its crystalline nature. 55 Another broad endothermic peak appeared at 80°C corresponding to the hydrophilic groups O-H group.…”
Section: Resultsmentioning
confidence: 95%
“…Entrapment efficiency was expressed as the percentage of drug entrapped in these prepared pectin-gelatin polyelectrolyte complex compared to the initial amount of the drug included in the formulation of all the samples, PG-1a (1:1 ratio of pectin and gelatin with 1ml of cross linker added) showed maximum drug encapsulation efficiency and hence this composition was chosen for drug release study. corresponds to oxidation region [13]. In case of the modified pectin (Fig.…”
Section: Uv-visible Spectral Analysismentioning
confidence: 94%
“…In this temperature range, it has been reported that the degradation is primarily derived from pyrolytic decomposition. It consists in a primary and secondary decarboxylation involving the acid side group and a carbon in the ring [59]. Moreover, the hydrolysis produces an increase in the evaporation temperature, going from 80°C for commercial pectin to higher values for all the hydrolyzed pectins.…”
Section: Process In This Workmentioning
confidence: 99%
“…The second degradation stage was very similar for either the pure or the modified pectin samples, although a slightly lower mass loss and a lower midpoint temperature were observed for the modified samples. The third stage, due to oxidative reactions, was postponed, particularly for linoleic residues, as expected for the oxygen scavenging effect of the double bonds [59]. To know more about different thermogravimetric studies of pectins with other compounds, the following references [60][61][62][63][64][65][66][67][68][69] can be read.…”
Section: Process In This Workmentioning
confidence: 99%